Educational Leadership & Learning Leadership - Triwiyanto, Teguh; Kusumaningrum, Desi Eri (Universitas Negeri Malang, 2024)
This literature research aims to identify the roots of terms, development of studies, and trends in educational leadership and learning leadership. A review was carried out on the literature with the keywords educational leadership and learning leadership, on various databases. For search purposes in the database, publish or perish is used. The research results show that the term educational leadership has its roots in the broader field of education and leadership studies, which is drawn from various scientific disciplines such as psychology, sociology, management, and organizational behavior. The term instructional leadership has deep roots in educational psychology, human development, and organizational learning theory. The development of educational leadership studies can be traced back to the late 19th and early 20th centuries, coinciding with the rise of formal schooling and the need for effective school administration. The development of learning leadership studies reflects the increasing recognition of the importance of the learning process in educational environments and organizational contexts. Several trends have emerged in the study of educational leadership and learning, reflecting shifts in educational paradigms, advances in technology, and the evolving needs of society.